Polymorphism of the proinflammatory and anti–inflammatory cytokines genes in patients with an acute pancreatitis in the Northern–Eastern region of Ukraine - I. D. Duzhyi; O. L. Sytnik; V. Ya. Pak (Клінічна хірургія)
Objective.To determine the influence of the genes polymorphism of proinflammatory – interleukin–8 A–251T (rs 4073) and antiinflammatory – interleukin–10 C–592A (rs 1800872) cytokines on course of an acute pancreatitis.